Perancangan Website UMKM Kafton Caffeine Space Menggunakan Platform Strikingly - Syafitri Anelia; Dhina Regina Putri; Zhafirah Fadhilah; Novadilastri .; Sularno . (CV. ITTC INDONESIA, 2026)
Kafton Caffeine Space is a Micro, Small, and Medium Enterprise (MSME) operating in the food and beverage (F&B) sector located in Batusangkar, Tanah Datar Regency, West Sumatra. One of the main challenges faced by this business is the absence of an official website as a medium for promotion and information dissemination, resulting in marketing activities being limited to social media platforms. This study aims to design and implement a website as a digital promotional medium for Kafton Caffeine Space using the Strikingly platform. This research was conducted as part of the implementation of Project Based Learning (PBL) in the Multimedia course of the Business Administration Study Program, Department of Business Administration, Politeknik Negeri Padang. The research employed a qualitative approach through observation and direct interviews with the business owner to identify content requirements, brand identity, target market, and promotional challenges faced by the business. The website was developed using the drag-and-drop features provided by Strikingly, allowing the development process to be carried out without requiring advanced programming skills. The results indicate that the developed website is capable of presenting business profile information, product menus, galleries, business location, and contact details in a more structured and accessible manner for customers. The website is expected to improve business visibility, expand promotional reach, and facilitate customer access to information regarding the products and services offered by Kafton Caffeine Space.